Three-dimensional laser scanning and numerical investigation on the influence of freeze-thaw and hang-wall mining on the instability of an open-pit slope - Zhang, Yanfei; Wu, Jihuan; Tang, Pufeng; Wang, Yu (Frontiers in Materials, 2023)
The instability of open pit slope and associated disasters of complex orebodies such as hanging wall mining are the key problems to be solved urgently in the development of western resources. In this work, taking the hanging wall mining in the open pit mine of Hejing iron mine for example, the disaster mechanism influenced by the coupling freeze-thaw and hanging wall mining is systematically studied by 3D laser scanning and numerical simulation. Firstly, the rock mass structure information such as dip, dip angle, spacing, and equivalent trace length characteristics were obtained using 3D intelligent recognition technology. Then, numerical simulation is employed to reveal the influence of freeze-thaw and excavation sequence on the overall stability of the open pit slope. The stress, displacement, plasticity zone and maximum shear strain patterns were revealed in detailed. The results show that the excavation engineering will lead to frequent increase and unloading of the internal stress of the rock mass, the gradual increase of the goaf area will cause great damage to the rock mass. The slope failure mode is strongly impacted by the freeze-thaw weathering and orebody excavation.